(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The elements of the crime composition distinguish its objective and subjective aspects in four cases. The elements of the crime composition are the object, subject, objective side, and subjective side of the crime. Its features, in turn, provide a description of the elements of the crime composition. They are connected to the elements as part of the object’s composition.